Evaluation of Two Methods for the Detection of Third Generation Cephalosporins Resistant Enterobacterales Directly From Positive Blood Cultures - Durand, Clarisse; Boudet, Agathe; Lavigne, Jean-Philippe; Pantel, Alix (Frontiers in Cellular and Infection Microbiology, 2020)
Due to the importance of a rapid determination of patients infected by multidrug resistant bacteria, we evaluated two rapid diagnostic tests for the detection of third-generation cephalosporins (3GC)-resistant Enterobacterales directly from positive blood cultures within 1 hour: BL-REDTM (electrochemical method) and β-LACTATM test (chromogenic method). A panel of 150 clinical strains characterized for their resistance profiles (e.g. penicillinases, extended-spectrum beta-lactamases (ESBLs), overproduction of cephalosporinase, carbapenemases, impermeability) was tested. Approximately 100 CFU of each isolate was spiked into sterile blood culture bottles and incubated in a BD BACTECTM FX automated system (Becton Dickinson, USA). Positive blood cultures were examined to parallel testing using the BL-REDTM and β-LACTATM tests and conventional susceptibility method (disc diffusion following EUCAST recommendations). For all phenotypes combined, the sensitivity, specificity, positive predictive value and negative predictive value in the detection of 3GC resistance were respectively i) with BL-REDTM: 45.7%, 100%, 100% and 54.2% and ii) with β-LACTATM test: 52.2%, 100%, 100% and 56.9%. The positivity of tests allows to adapt antibiotic treatment whereas the negative result requires other tests. Moreover, these tests detect most Ambler class A-producing Enterobacterales (KPC, ESBL, extended-spectrum OXY) with sensitivities and specificities of 87.5% and 99% for BL-REDTM respectively and both 100% for β-LACTATM test (47/47 isolates). These two rapid tests failed to detect AmpC overexpressed (sensitivities of 2.7% for BL-REDTM and 0% for β-LACTATM test) and Ambler class B-producing Enterobacterales (sensitivities of 40% for both tests) notably strains without ESBLs associated (sensitivities of 0% for both tests). BL-REDTM and β-LACTATM tests are easy-to-use and mainly attractive when a positive result is obtained notably to detect most of the Ambler class A-producing Enterobacterales in less than one hour after the positivity of the blood culture, allowing a rapid adaptation of the antibiotic therapy in patients.